2022
DOI: 10.3390/biomedicines10030541
|View full text |Cite
|
Sign up to set email alerts
|

ICG-Guided Lymphadenectomy during Surgery for Colon and Rectal Cancer—Interim Analysis of the GREENLIGHT Trial

Abstract: Lymphadenectomy is crucial for an optimal oncologic resection of colon and rectal cancers. However, without a direct visualization, an aberrant route of lymph node (LN) diffusion might remain unresected. Indocyanine-green (ICG) lymphatic mapping permits a real-time LNs visualization. We designed the GREENLIGHT trial to explore in 100 patients undergoing robotic colorectal resection the clinical significance of a D3 ICG-guided lymphadenectomy. The primary endpoint was the number of patients in whom ICG changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Apart from brain tumors, efforts are underway to extend FGR to other organ systems as well, not only using 5-ALA [ 17 , 18 , 19 , 20 ], but also other fluorochromes, and study designs resulting in regulatory approval are being intensely discussed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from brain tumors, efforts are underway to extend FGR to other organ systems as well, not only using 5-ALA [ 17 , 18 , 19 , 20 ], but also other fluorochromes, and study designs resulting in regulatory approval are being intensely discussed [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the interim analysis of the GREENLIGHT trial, [ 72 ] a prospective non-randomized trial of ICG lymphatic mapping, showed that the extent of the lymphadenectomy was modified based on the results of imaging in 50% of the study population (35/70). What was more interesting is that they demonstrated that lymph node metastasis was not correlated with a paucity in ICG signal, as was shown in previous studies.…”
Section: Current Uses Of Icg In Colorectal Surgerymentioning
confidence: 99%
“…Since ICG was initially applied to guide the resection of brain tumors, its application in tumor diagnosis and surgical navigation has been pursued actively. Moreover, fluorescence imaging (FLI) in the second near‐infrared window (NIR‐II) of ICG has been further investigated and utilized in recent years [5–10] …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fluorescence imaging (FLI) in the second near-infrared window (NIR-II) of ICG has been further investigated and utilized in recent years. [5][6][7][8][9][10] Despite the advantages mentioned above, the features such as passive tumor uptake and the short half-life of free ICG still limit its clinical application in accurate tumor imaging, especially the accurate identification of tumor margins in tumor operation. Therefore, developing ICG-labeled probes for tumorspecific targets will conquer the obstacles in clinical practice.…”
Section: Introductionmentioning
confidence: 99%